Photovoltage improvements in Cz-Si by low-energy implantation of carbon ions - Nadtochiy, A; Korotchenkov, O; Romanyuk, B; Melnik, V; Popov, V (Materials Research Express, 2016)
We demonstrate photovoltage improvements in Czochralski-grown silicon wafers by low-energy implantation of carbon ions. After annealing at temperatures above 550 °C the surface photovoltage (SPV) increases in both implanted and unimplanted sample sets. The increase in the SPV signal observed in implanted samples, which are subsequently annealed at 650 °C and 750 °C, is roughly two times greater than the appropriate values observed in unimplanted wafers. The effect in implanted samples is accompanied by longer time decays in the SPV transients (roughly from several to hundreds of microseconds). In marked contrast, unimplanted samples do not show such a significant difference in the decay times upon annealing. The decay times are fairly evenly distributed across the surface of the implanted but unannealed wafer, whereas the surface distribution function is essentially non-uniform in annealed samples. The results are discussed in terms of the temperature specific defect chemistry. The results of this work open new possibilities for studying defect rearrangement and clustering of atoms in implanted Si and advancing the development of silicon based photovoltaic materials with high photovoltage response. Supplementary data are available from stacks.iop.org/SST/.